The effect of triceps brachii fatigue on shot accuracy of male and female basketball players - Rashid, D. M. S.; Faraj, S. M. S.; Hedayatpour, N. (International Journal of Performance Analysis in Sport, 2020)
Previous studies demonstrated that the presence of neuromuscular fatigue within the triceps brachii muscle was accompanied by decreasing accuracy in throwing motion; however, sex differences in triceps brachii fatigability and throwing accuracy have not yet been investigated. The aim of the current study was to investigate the differences between female and male in measures of triceps brachii fatigability and basketball shooting accuracy after a fatiguing exercise. Twelve male (age, mean ± SD; 16.±1.4 yr) and twelve female (age, mean ± SD; 16 ± 1.2 yr) with no major medical history participated in the laboratory-based study. Basketball shooting accuracy, maximal voluntary contraction force and muscular endurance of the triceps brachii muscle measured before and after a fatiguing exercise. Maximal voluntary contraction force, endurance time of the triceps brachii muscle and basketball shooting accuracy significantly reduced after fatiguing exercise (P < 0.05), with a higher reduction identified for the male as compared to female (P < 0.05). The result suggests a significant effect of sex differences on triceps brachii fatigability and basketball shooting accuracy after fatiguing exercise, most likely due to sex differences in muscle fibre type composition. However, future research is required to confirm sex-specific differences in motor skill accuracy after fatiguing exercise.